UPAYA ASEAN DALAM MENYELESAIKAN KONFLIK LAUT CINA SELATAN TAHUN 2010-2015 - Anugerah Baginda Harahap; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes roles of ASEAN in resolution conflict of South China Sea in 2010-2015. South China Sea are one of High Seas in International seas that have a 3,5 million mil. South China Sea has a big potency in a mineral resources and as a international matirim ways. Since 1974 Tiongkok has claim South China Sea as a their territory and it’s make a complain from the ASEAN member state especially Indonesia, Malaysia, Brunei Darusalam, Vietnam and Filiphina.The writer collects data from books, encyclopedia, journal, mass media and websites to analyze the roles of ASEAN in resolution conflict of South China Sea. The theories applied in this research are pliralism perspective with the international organization theory by Clive Archer.The result of this research shows that the roles of ASEAN in resolution conflict of South China Sea are used by diplomacy ways approach and instrument of international law. Some effort of ASEAN are in 2011 ASEAN has implemented code of Conduct dan Declaration on the Conduct (DOC) of Parties in the South Tiongkok Sea, ASEAN member has optimaled ASEAN Regional Forum ways and ASEAN Political Security Community in resolution conflict of South China Sea and ASEAN members held a ministrial meeting to create a peacefull in South Cina Seas territory.Key words: roles, ASEAN, conflic, South China Sea.